Geochemical peculiarities of nitric thermal waters in Jiangxi Province (SE-China) - Sun, Z.; Shvartsev, Stepan Lvovich; Tokarenko, Olga Grigorievna; Zippa, E.V.; Gao, B. (IOP Publishing, 2016)
The chemical composition of nitric thermal waters in Jiangxi Province, SE-China, is considered. It is shown that the studied thermal waters are characterized by low TDS (293-412 mg/l), but they always have alkaline or highly alkaline pH values. It should be noted that the content of Na{+}, Si, F{-}, HCO[3]{-}, CO[3]{2-}, sometimes SO[4]{2-} is predominant, on the other hand, the content of Ca{2+}, Mg{2+}, Cl{-} is low. It has been established that the main factors responsible for low concentrations of some chemical elements and high concentrations of others are continuous dissolution of aluminosilicate minerals and simultaneous precipitation of the secondary minerals.
Keywords: геохимические особенности; азотные термальные воды; термальные воды; Китай; алюмосиликатные материалы; вторичные минералы